Comparison between Volar Locking Plate and Kirschner Wire Fixation for Unstable Distal Radius Fracture: A Meta-Analysis of Randomized Controlled Trials - Tariq, Muhammad A.; Ali, Uzair; Uddin, Qazi S.; Altaf, Zahabia; Mohiuddin, Ashar (Journal of Wrist Surgery, 2023)
Objective This study aims to compare the outcomes of volar locking plating (VLP) versus percutaneous Kirschner wires (K-wire) fixation for surgical management of unstable distal radius fractures.Methods We systematically searched multiple databases, including MEDLINE, EMBASE, Cochrane Central till January 2022 for randomized controlled trials (RCTs) that met eligibility criteria. Following outcomes were evaluated at 6-week, 3-, 6-, and 12-month follow-up period: Disabilities of the Arm, Shoulder, and Hand (DASH) score, Patient Rated Wrist Evaluation (PRWE) score, grip strength, range of motion, and complication incidence. Meta-analysis was performed using random effects models and results presented as risk ratios (RRs) or mean differences (MDs) with 95% confidence interval.Results Fourteen RCTs with 1,450 participants met the inclusion criteria. DASH scores were significantly better for VLP fixation at 6th week (MD = 19.02; p < 0.001), 3rd (MD = 10.79; p < 0.001), 6th (MD= 7.78; p < 0.001), and 12th month (MD = 2.94; p < 0.001) postoperation. At 3-month follow-up period, VLP treatment exhibited better grip strength (MD = − 10.32; p < 0.001) and PRWE scores (MD = 8.78; p < 0.001). There was a statistically significant early advantage in flexion, extension, pronation, supination, radial deviation, and ulnar deviation in the VLP group at 6-week follow-up, but at 1-year follow-up only significantly better extension was observed. At 1 year, radiographic outcomes were similar except for volar tilt favoring VLP fixation (p < 0.001). Superficial infections were more common in patients treated with K-wire (RR = 2.89; p = 0.001), but there was no difference in total complications or reoperation rates (p > 0.05).Conclusion This meta-analysis suggests that VLP fixation and K-wire fixation are both effective procedures, but existing literature does not provide sufficient evidence to demonstrate the superiority of either method. Although VLP fixation improves DASH score, extension and volar tilt at 12-month follow-up, the difference is small and unlikely to be noticeable to the patients.
Keywords: distal radius fracture; Kirschner wire; meta-analysis; volar locking plating